DRIP IRRIGATION WETTING PATTERNS IN A MID FLORIDA SANDY SOIL - Alves Júnior, José; Bandaranayake, Wije Mallikaara; Syvertsen, James (IRRIGA, 2018)
DRIP IRRIGATION WETTING PATTERNS IN A MID FLORIDA SANDY SOIL JOSÉ ALVES JÚNIOR1; WIJE MALLIKAARACHCHIGE BANDARANAYAKE2 E JAMES SYVERTSEN2 1Eng. Agr. Professor Adjunto da Escola de Agronomia (EA) da Universidade Federal de Goiás (UFG), Avenida Esperança, s/n, Campus Samambaia, Goiânia, Goiás, Brasil, CEP: 74.690-900. jose.junior@pq.cnpq.br 2Professor and Researcher in University of Florida, IFAS, CREC, Lake Alfred-FL 33850, USA. wijeb@ufl.edu, jmsn@ufl.edu 1 ABSTRACT The wetting pattern of soil under drip irrigation is governed by soil texture, structure, initial water content, emitter spacing, discharge rate and irrigation frequency. Although drip irrigation is not common in central Florida “Ridge soils”, the “advanced citrus production system” can hold a promising future. High frequency, short duration pulses is an important factor to consider for efficient irrigation in this very sandy “Ridge” soils. The objective of this research was to evaluate the water distribution pattern under 1.9, 4.6 and 8.6 L h-1 discharge rate drippers over different wetting durations using three evaluation methods: a) EC5 soil water sensors, b) blue dye tracer, and c) a simple mathematical model developed for sandy soils. Of the three methods, the dye method is labor intensive and time consuming and was used only to evaluate one pulse rate with 3 pulse durations. Soil water sensors, though relatively expensive, gave the most detailed wetting patterns under different combinations of pulse rates and wetting durations. The model overestimated the wetting depth and underestimated the wetting diameter. With the initial soil moisture at 0.055 m3 m-3 and a constant application pressure of 138 kPa, the maximum achievable wetting diameter with increasing pulse rate and pulse duration was limited to 0.75 m. However, the wetting depth increased >1 m with >4.63 L h-1 pulse rate and 3-h duration. Preferential flow was minimal but had little influence on wetting pattern. The best combination was the 4.63 L h-1 emitter with a 3 h pulse that yielded the maximum wetting diameter (0.77 m) and the optimum wetting depth (0.77 m). Keywords: Trickle irrigation, soil water sensors, FD&CC blue dye, soil water movement, water use efficiency. ALVES JÚNIOR., J.; BANDARANAYAKE, W. M.; SYVERTSEN, J. BULBO MOLHADO SOB IRRIGAÇÃO POR GOTEJAMENTO EM SOLO ARENOSO NA FLORIDA 2 RESUMO O padrão de umedecimento do solo sob irrigação por gotejamento é regido pela textura do solo, a estrutura, o conteúdo inicial de água solo, espaçamento entre emissores, a vazão do emissor e freqüência de irrigação. Embora, a irrigação por gotejamento não seja comum no centro da Flórida, no "sistema avançado de produção de citros" pode conter um futuro promissor. Alta freqüência, pulsos de curta duração é um fator importante a considerar para irrigação eficiente neste solo arenoso. O objetivo deste trabalho foi avaliar o padrão de distribuição de água em diferentes vazões de gotejadores 1,9, 4,6 e 8,6 L h-1 ao longo de diferentes períodos de molhamento usando três métodos de avaliação : a) sensores de água no solo EC5 , b) corante azul , e c) um modelo matemático simples. Dos três métodos, o método do corante é trabalhoso e consome muito tempo, e por isso só foi utilizado para avaliar uma vazão em 3 diferentes tempos de irrigação. Sensores de água no solo, apesar de relativamente caro, deu os padrões de molhamento mais detalhados sob diferentes combinações de vazão e tempo de irrigação. O modelo superestimou a profundidade molhada e subestimou o diâmetro molhado. Com a umidade do solo inicial de 0,055 m3 m-3 e uma pressão de aplicação constante de 138 kPa, o diâmetro molhado máximo obtido entre as vazões e tempos de irrigação avaliados foi de 0,75 m. No entanto, profundidade molhada ultrapassa 1 m, com 4,63 L h-1 de vazão do gotejador e 3 h de tempo de irrigação. Fluxo preferencial foi mínimo, mas teve pouca influência sobre o bulbo molhado. A melhor combinação foi a vazão de 4,63 Lh-1 com um tempo de 3 h, que produziu o diâmetro máximo de molhagem (0,77 m) e a profundidade de molhagem óptima (0,77 m). Palavras-Chave: Irrigação localizada; sensors de água no solo; FD&CC blue dye; movimento de água no solo